2019
DOI: 10.17718/tojde.640495
|View full text |Cite
|
Sign up to set email alerts
|

The Utilitarian vs. Hedonic Teacher Acceptance of ICT Use

Abstract: This research examined which teachers' cognitive and motivational factors, i.e., constructivist beliefs, intrinsic and extrinsic motivation, perceived ease of use and behavioral intention, fostered an effective and satisfactory integration of technology into educational practices. 374 Italian teachers (M Age = 38.69, SD = 5.30; F = 198) attending a training course in ICT were divided into two groups: the first with less than 20 years of teaching experience, the second with more than 21 years. Participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…The willingness of academic staff to adopt online teaching is an excellent opportunity for the universities in Tanzania to invest in online teaching. This concurs with a study by [ 32 – 34 ], which found that human resource readiness positively influences e-learning implementation. However, a continuous, supporting environment with an internet connection and laptop availability should be prioritised to support online course delivery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The willingness of academic staff to adopt online teaching is an excellent opportunity for the universities in Tanzania to invest in online teaching. This concurs with a study by [ 32 – 34 ], which found that human resource readiness positively influences e-learning implementation. However, a continuous, supporting environment with an internet connection and laptop availability should be prioritised to support online course delivery.…”
Section: Discussionsupporting
confidence: 92%
“…However, a continuous, supporting environment with an internet connection and laptop availability should be prioritised to support online course delivery. In addition, the results of this study support the findings of other studies [ 34 , 35 ] that indicated the main obstacles which discourage academics from online course teaching are technical problems during course preparation and course delivery and a sense of excessive mechanisation of the learning process.…”
Section: Discussionsupporting
confidence: 88%
“…The implementation of user-friendly software and platforms also has a significant impact on the success of the whole process [7]. The ease of using IT solutions in e-learning classes and the perceived usefulness of e-learning classes are key factors determining the acceptance of this form of teaching by lecturers [32][33][34].…”
Section: Educators' Approach To E-learningmentioning
confidence: 99%
“…An extrinsic motivational factor, on the other hand, can be derived from a utilitarian value that results from a perceived overall usefulness (Davis, 1989;Limone et al, 2019). In this study, students attributed the perceived overall usefulness of their group chats to refining their understanding of the course's syllabus, clarifying their doubts and misconceptions, and improving their proficiency in the German language.…”
Section: Likelihood Of Utilising Chatmentioning
confidence: 91%